Tetraserica Ahrens, 2004 of continental Southeast Asia: new records, new species, and an updated key to species (Coleoptera: Scarabaeidae: Sericinae: Sericini) - Ahrens, Dirk; Lukic, Daniel; Pham, Phu; Li, Wei; Liu, Wangang (Zootaxa, 2023)
An update to the taxonomy and distribution of species of Tetraserica Ahrens, 2004 (Coleoptera: Scarabaeidae) is given. We present new records of 36 taxa and describe 13 new species from continental Southeast Asia: Tetraserica bartolozzii Ahrens, new species, T. bankrang Ahrens, new species, T. sraeken Ahrens, new species, T. yongbelar Ahrens, new species, T. hubleyi Ahrens, new species, T. hornburgi Ahrens, new species, T. khemoi Ahrens, new species, T. weigeli Ahrens, new species, T. yucheni Liu, Li & Ahrens, new species, T. fabriziae Liu, Li & Ahrens, new species, T. gialaiensis Pham & Ahrens, new species, T. phamanhi Pham & Ahrens, new species, and T. semikontumensis Pham & Ahrens, new species. The male genitalia of the new species are illustrated and diagnostic characters to related species are given. The key to species of continental Southeast Asia is updated.